2008
DOI: 10.1542/peds.2007-2758
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Pediatric Neuromyelitis Optica

Abstract: Pediatric neuromyelitis optica has a diverse clinical presentation and may be difficult to distinguish from multiple sclerosis in the early stages of the disease. The recognition of the broad spectrum of this disease to include signs and symptoms of brain involvement is aided by the availability of a serum biomarker: neuromyelitis optica immunoglobulin G. Early diagnosis and immunosuppresive treatment may help to slow the accumulation of severe disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 27 publications
5
137
1
Order By: Relevance
“…Several studies have reported cases of MS and NMO with SIADH (18)(19)(20)(21)(22)(23)(24). In the majority of these reported cases, demyelinating lesions in the hypothalamus have been detected on brain MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported cases of MS and NMO with SIADH (18)(19)(20)(21)(22)(23)(24). In the majority of these reported cases, demyelinating lesions in the hypothalamus have been detected on brain MRI.…”
Section: Discussionmentioning
confidence: 99%
“…While these patients may also have had SS, they either did not otherwise meet diagnostic criteria for SS (because of the lack of salivary gland biopsies) 10 or specific details concerning SS diagnosis were not published 4 . Clinical and imaging findings possibly consistent with an NMOSD along with definitive SS have also been reported, but the diagnosis of an NMOSD was not confirmed because no NMO-IgG results were reported 8,11 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Dysphagia has been reported in a few NMO patients in association with other symptoms (4,5). Hiccups, nausea and vomiting presumably occur due to the involvement of the area postrema, located in the dorsal medulla.…”
Section: Isolated Dysphagia Due To Aquaporin-4 Autoimmunitymentioning
confidence: 99%